Evaluation of fungicide applications to sweet orange at different flowering stages for control of postbloom fruit drop caused by Colletotrichum acutatum - de Goes, A. [UNESP]; Garrido, R. B. O. [UNESP]; Reis, R. F. [UNESP]; Baldassari, Ricardo Braga [UNESP]; Soares, M. A. (Elsevier B.V., 2008)
Postbloom fruit drop (PFD), caused by Colletotrichum acutatum, produces blossom blight, fruit abscission and persistent calyces. in groves of Pera-Rio and Natal sweet orange located in Santa Cruz do Rio Pardo and Rincao, São Paulo, Brazil, four experiments were carried out to evaluate the effectiveness of fungicides sprayed alone or as mixtures, at different flowering stages for the control of PFD of citrus. The number of symptomatic flowers, the percentage of fruit set (FS), and the relationship between persistent calyces and total fruit weight per plant were evaluated. The fungicides carbendazim and folpet were sprayed at 0.50 ml and 1.25 ga.i. l(-1) of water, respectively, were superior by all the criteria to the other treatments. Carbendazim and folpet fungicides performed best when they were applied at the green bud through hollow ball stages. Difenoconazole, independent of application timing, was less effective by all criteria used. Application of mancozeb at 1.60 ga.i. l(-1) at the green bud stage followed by application of mancozeb in a tank mix with carbendazim or folpet at 1.0 ml and 1.25 g a.i. l(-1), respectively, during green bud bloom and hollow ball stages were effective for disease control. Carbendazim combined with 0.25% KNO3, reduced the number of persistent calyces and increased fruit production significantly. Applications must be made between green bud and hollow ball stages for best control. Applications only at hollow ball or open flower stages did not provide effective disease control. (C)2007 Elsevier Ltd. All rights reserved.
Keywords: Citrus sinensis; blossom blight; Flowers